Impact of mental fatigue on speed and accuracy components of soccer-specific skills. Issue 1 (2nd January 2017) - Smith, Mitchell R.; Fransen, Job; Deprez, Dieter; Lenoir, Matthieu; Coutts, Aaron J.
ABSTRACT: This study examined the impact of mental fatigue on speed and accuracy components of soccer-specific skills. Fourteen well-trained soccer players completed the Loughborough Soccer Passing Test on two occasions, separated by a minimum of 48 h. Tests were preceded, in a randomised order, by 30 min of reading magazines (control) or the Stroop task (mental fatigue). Subjective mental fatigue was recorded on visual analogue scales before and after reading. Mental effort (referring to the reading task) and motivation (for the upcoming passing test) were recorded after reading. Soccer-specific skill performance was assessed using time taken to complete all passes, and number of errors committed. Mental fatigue and effort were higher following the Stroop task than the magazines ( P < 0.001), while motivation was similar between conditions. Time taken to complete the passing test was similar between conditions; however, players committed more missed target errors (2.4 ± 1.3 s vs. 1.6 ± 1.1; P = 0.02) and less perfect passes (5.6 ± 1.4 s vs. 6.6 ± 1.5; P = 0.04) in the mental fatigue condition, while no other errors were significantly different between conditions. Mental fatigue impairs short passing accuracy, but not movement speeds during the Loughborough Soccer Passing Test.